Phytochemical Screening And Antioxidant Activity Of Euryale Ferox Leaf Extract: An Untapped Botanical Resource - Chaudhary, Varsha; Vishwakarma, Dhirendra; Kesharwani, Roohi; Gupta, Paras; Srivastava, Vineet; Yadav, Priyanka; Sameem, Shahnawaz (Journal of Neonatal Surgery, 2025)
Oxidative stress caused by reactive oxygen species (ROS) is a major contributor to the pathogenesis of several chronic diseases. Euryale ferox, traditionally recognized for its nutritional and medicinal properties, has been extensively studied for its seeds, while its leaves remain largely unexplored. This study investigates the antioxidant potential of E. ferox leaf extract using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging assay. Leaves were collected, shade-dried, and extracted with 70% ethanol. Antioxidant activity was evaluated by measuring DPPH radical scavenging, with ascorbic acid as the reference standard. The extract exhibited a concentration-dependent free radical scavenging effect. The IC₅₀ value of the E. ferox leaf extract was found to be 71.18 ± 0.0691 µg/mL compared to 19.21±0.051 µg/mL, for ascorbic acid, indicating moderate to strong antioxidant activity. These results suggest that E. ferox leaves contain significant levels of polyphenolic and flavonoid compounds responsible for their antioxidant activity, supporting their potential use as a natural antioxidant in pharmaceutical and nutraceutical formulations.